Work-related musculoskeletal disorders in anesthesiologists: A cross-sectional study on prevalence and risk factors (Annals of Medical Research, 2021)
Aim: To investigate the prevalence of self-reported work-related musculoskeletal disorders (WRMDs) of anesthesiologists, to evaluate potential risk factors, including personal and workload characteristics and working ergonomics.Material and Methods: A cross-sectional international survey including personal and workload characteristics of anesthesiologists was conducted. The Standardized Nordic Musculoskeletal Questionnaire was used to identify working ergonomics and the quality of ergonomic conditions of the operating room. The prevalence of WRMDs was calculated, and predictors of these symptoms were evaluated using binary logistic regression.Results: 98.4% of respondents reported a WRMD in the previous 12 months, mainly low back disorders (70.7%). Cardiothoracic anesthesiologists were more likely to report 12-month knee problems (66%). Overall, pediatric anesthesiologists were more likely to report 12-month WRMDs in most of their body sites. Women were more likely to develop WRMDs in the upper back (OR=2.465; 95% CI:1.061-5.729) as compared with men. Long-duration bending was the most significant ergonomic hazard for all 3 body regions of musculoskeletal symptoms, with an OR of 4.210 (95% CI:1.081-16.391) for the neck, 4.619 (1.274-16.744) for the upper back, and 4.750 (1.045-21.590) for the low back. Suboptimal quality of ergonomic conditions in the operating room was significantly associated with increased WRMDs risk of the neck (OR=0.346; 95% CI:0.147- 0.812) and shoulder (OR=0.405; 95% CI:0.167- 0.982) regions. Conclusion: Anesthesiologists are at high risk for WRMDs. There is a need to improve ergonomic conditions of operative rooms according to demands of anesthesiologists and to educate them on proper posture for a longer and pain-free career.Keywords: Anesthesiologist; ergonomics; work-related musculoskeletal disorders; posture; survey.